Triple "A" syndrome presenting as recurrent chronic sinusitis with Pneumonia, septic shock and meningoencephalitis in a child - Ramaning Loni; Priyanka Agrawal; Prashant Rajebhosale; Mrutyunjaya Panda; Prashant Darveshi; Prakash Valse (Wolters Kluwer Medknow Publications, 2018)
Triple A syndrome (All grove syndrome) is a rare autosomal recessive disorder characterized by the clinical triads of adrenal insufficiency, achalasia cardia and alacrimia with variable association of autonomic and neurological manifestations. Nearly100 cases have been reported all over world however in India, only 2 to 3 cases have reported. We present 13 years old boy with chronic recurrent sinusitis with failure to thrive without lacrimation since birth who had presented recurrent chronic sinusitis with pneumonia, septic shock, and acute meningoencephalitis with adrenal insufficiency. Catastrophic complications can be prevented with adequate cortisol and specific measures such as cardiac pneumatic dilatation or myotomy along with other supportive management.